2008 IEEE/RSJ International Conference on Intelligent Robots and Systems 2008
DOI: 10.1109/iros.2008.4650815
|View full text |Cite
|
Sign up to set email alerts
|

A random set formulation for Bayesian SLAM

Abstract: This paper presents an alternative formulation for the Bayesian feature-based simultaneous localisation and mapping (SLAM) problem, using a random finite set approach. For a feature based map, SLAM requires the joint estimation of the vehicle location and the map. The map itself involves the joint estimation of both the number of features and their states (typically in a 2D Euclidean space), as an a priori unknown map is completely unknown in both landmark location and number. In most feature based SLAM algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…The reader is referred to the work of Mullane et al [9], [10] and Lee, Clark & Salvi [12], [13] for an in-depth treatment of the PHD-based SLAM methods. Additionally, the reader is referred to the works of Mahler, B.-N. Vo, B.-T. Vo, Ristic and Clark [7], [15]- [21] for further information on PHD filters.…”
Section: Single Cluster Phd Slammentioning
confidence: 99%
“…The reader is referred to the work of Mullane et al [9], [10] and Lee, Clark & Salvi [12], [13] for an in-depth treatment of the PHD-based SLAM methods. Additionally, the reader is referred to the works of Mahler, B.-N. Vo, B.-T. Vo, Ristic and Clark [7], [15]- [21] for further information on PHD filters.…”
Section: Single Cluster Phd Slammentioning
confidence: 99%
“…given the x and y-coordinates of the Gaussian components, and expressed in the vehicle's coordinate frame E. Furthermore, assume that the left and right edge of the road are approximately parallel and that they can be modeled using at most K polynomials (22). The polynomials only differ by the lateral distances a…”
Section: Road Edge Estimationmentioning
confidence: 99%
“…are derived by using the road border model (22) and the parametersθ (1) andθ (2) , respectively. The coordinates form the mean values of the position of the Gaussian components on the road edges according to…”
Section: B Spawn Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed Bayesian FB-SLAM framework allows for the joint, on-line estimation of the vehicle trajectory, the feature locations and the number of features in the map. Preliminary studies using 'brute force' implementations can be found in [10], [11], [12]. In this paper, a tractable first order solution, coined the PHD-SLAM filter, is derived, which jointly propagates the posterior PHD or intensity function of the map and the posterior distribution of the trajectory of the vehicle.…”
Section: Introductionmentioning
confidence: 99%